Premalignant Changes in the Bronchial Epithelium Are Prognostic Factors of Distant Metastasis in Non-Small Cell Lung Cancer Patients - Pankova, Olga V.; Tashireva, Liubov A.; Rodionov, Evgeny O.; Miller, Sergey V.; Tuzikov, Sergey A.; Pismenny, Dmitry S.; Gerashchenko, Tatiana S.; Zavyalova, Marina V.; Vtorushin, Sergey V.; Denisov, Evgeny V.; Perelmuter, Vladimir M. (Frontiers in Oncology, 2021)
The study assessed the possibility of dividing patients into groups based on the assessment of morphological changes in the epithelium of small-caliber bronchi located near the primary tumor in order to predict a high and low risk of distant metastasis of non-small cell lung cancer. In 171 patients with non-small cell lung cancer (T1-4N0-3M0) in small-caliber bronchi taken at a distance of 3-5 cm from the tumor, various variants of morphological changes in bronchial epithelium (basal cell hyperplasia, squamous cell metaplasia, dysplasia) were assessed. Long-term results of treatment, namely distant metastasis, were assessed after 2 and 5 years. During the follow-up period, distant metastases were found in 35.1% (60/171) of patients. Most often they were observed in patients of the high-risk group – BCH+SM–D– (51.6%, 40/95) and BCH–SM+D+ (54.4%, 6/11). Less often distant metastases were observed in low-risk group patients – BCH+SM+D– (6.7%, 3/45) and BCH–SM–D– (10.0%, 2/20). Tumor size, grade and stage were significant predictors of metastasis only in the high-risk group. 5-year metastatic-free survival was better in the low-risk group of distant metastases. Isolated BCH or dysplasia in small bronchi distant from foci of tumor is associated with a high-risk distant metastasis and less 5-year metastatic-free survival.